The Borders of Punishment: Migration, Citizenship, and Social Exclusion - Franko, Katja (OUP Oxford, 2013)
The Borders of Punishment: Migration, Citizenship, and Social Exclusion critically assesses the relationship between immigration control, citizenship, and criminal justice. It reflects on the theoretical and methodological challenges posed by mass mobility and its control and for the first time, sets out a particular sub-field within criminology, the criminology of mobility. Drawing together leading international scholars with newer researchers, the book systematicallyoutlines why criminology and criminal justice should pay more attention to issues of immigration and border control.Contributor